The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/10406387221078047
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plasma cell-free DNA as a potential biomarker in horses

Abstract: Plasma cell-free DNA (cfDNA) is a biomarker of ischemia, systemic inflammation, and mortality in humans with gastrointestinal disease. Cell-free DNA has not been investigated as a biomarker for equine colic, to our knowledge. We hypothesized that cfDNA could be measured accurately in neat equine plasma using a benchtop fluorometer and that plasma cfDNA would be elevated in emergency patients compared to healthy horses. Plasma was obtained from blood collected in Roche DNA stabilizing tubes. We used the Qubit 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…The small CV found for the cfDNA assay in horses is consistent with the mean CV (2%) using the same analytical method reported in dogs [ 75 ] and a report that used the assay in horses admitted as emergency patients with colic and a control group [ 70 ]. The precision of the assay meets the USA Food and Drug Administration’s requirements for bioanalytical method validation (Food and Drug Administration, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The small CV found for the cfDNA assay in horses is consistent with the mean CV (2%) using the same analytical method reported in dogs [ 75 ] and a report that used the assay in horses admitted as emergency patients with colic and a control group [ 70 ]. The precision of the assay meets the USA Food and Drug Administration’s requirements for bioanalytical method validation (Food and Drug Administration, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Even though, a similar lack of diagnostic sensitivity was demonstrated in a recent study in foals that showed no significant differences in cfDNA concentrations between critically ill and healthy foals [ 39 ], suggesting that even with significant systemic illness, plasma cfDNA concentration may not be a useful marker in young horses. In contrast, cfDNA is significantly higher in emergency patients > 2 years old with colic than in control horses and ponies [ 70 ]. In the current OA model, plasma cfDNA measurement was not sufficiently sensitive for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Similarly, plasma cell–free DNA, a marker that can also be increased as a result of NET release, was elevated in equine colic patients. 4 However, the presence of infectious processes was not confirmed in these studies. 3 , 4 Interestingly, plasma cell–free DNA concentrations were not elevated in septic foals.…”
mentioning
confidence: 65%
“…A recent study evaluated the utility of this marker in equine patients presented to a referral centre, in which the majority of cases were admitted for colic. 45 Results showed that the levels of cfDNA were higher in sick compared with healthy horses, including in the colic subgroup. The relatively small number of cases (50 horses), particularly colic cases (36 horses) which was the main goal of the study, somewhat limits the conclusions that can be made.…”
Section: Other Biomarkersmentioning
confidence: 93%
“…Plasma cell‐free DNA (cfDNA; generated from cellular apoptosis and necrosis) is a biomarker used in humans for the diagnosis and prognosis of several conditions, including acute abdominal pain. A recent study evaluated the utility of this marker in equine patients presented to a referral centre, in which the majority of cases were admitted for colic 45 . Results showed that the levels of cfDNA were higher in sick compared with healthy horses, including in the colic subgroup.…”
Section: Other Biomarkersmentioning
confidence: 99%